On the Hydrogen-Ion Concentration in the Alimentary Canal of Certain Orthopteroid Insects. - Srivastava, Uma Shanker; Srivastava, P. D. (Beiträge zur Entomologie = Contributions to Entomology, 1956)
The hydrogenion concentration of the foregut, midgut and hindgut in the fifteen species of orthopteroid insects studied ranges from 5.4 to 6.6, 6.0 to 6.8 and 5.4 to 7.0 respectively. The data at our disposal leads us to the following conclusions: -(1) that different groups of insects may differ widely from each other in respect to the pH of the alimentary canal but within a group the range of variation is limited and determined by the group to which the insects belong;(2) that, while insects with different feeding habits may show different midgut pH, the midgut pH of the same insect is not markedly affected by different food given to it, i. e., the midgut pH shows a ’constancy’; (3) that the pH in the foregut and the hindgut may show a variation with change of food; and (4) that there exists a marked degree of correspondence between the pH of the midgut and that of the blood.